Comprehensive medication management services provided via telehealth or hybrid models: A scoping review. Issue 1 (13th December 2022) - Amundson, Collin; Marupuru, Srujitha; Kliethermes, Mary Ann; Axon, David R.; Warholak, Terri L.; Turgeon, Jacques; Bingham, Jennifer M.
Abstract: Comprehensive medication management (CMM) is increasingly provided by health care teams through telehealth or hybrid modalities. The purpose of this scoping literature review was to assess the published literature and examine the economic, clinical, and humanistic outcomes of CMM services provided by pharmacists via telehealth or hybrid modalities. This scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis extension for Scoping Reviews. Randomized controlled trials (RCTs) and observational studies were included if they: reported on economic, clinical, or humanistic outcomes; were conducted via telehealth or hybrid modalities; included a pharmacist on their interprofessional team; and evaluated CMM services. The search was conducted between January 1, 2000, and September 28, 2021. The search strategy was adapted for use in Medline (PubMed); Embase; Cochrane; Cumulative Index to Nursing and Allied Health Literature; PsychINFO; International Pharmaceutical Abstracts; Scopus; and grey literature. Four reviewers extracted data using a screening tool developed for this study and reviewed for risk of bias. Authors screened 3500 articles, from which 11 studies met the inclusion criteria (9 observational studies, 2 RCTs). In seven studies, clinical outcomes improved with telehealth CMM interventions compared to either usual care, face‐to‐face CMM, or educational controls, as shown by the statistically significant changes in chronic disease clinical outcomes. Two studies evaluated and found increased patient and provider satisfaction. One study described a source of revenue for a telehealth CMM service. Overall, study results indicate that telehealth CMM services, in select cases, may be associated with improved clinical outcomes, but the methods of the included studies were not homogenous enough to conclude that telehealth or hybrid modalities were superior to in‐person CMM. To understand the full impact on the Quadruple Aim, additional research is needed to investigate the financial outcomes of CMM conducted using telehealth or hybrid technologies.